Differences in The Company's Financial Performance Before And After Corporate Action On The Indonesia Stock Exchange - Putra, Buja Andri Kisa; Fatimah, Fatimah; Choiriyah, Choiriyah; Moelyatie, Trisniarty Adjeng (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2022)
This study aims to determine the differences in the company's financial performance before and after corporate action on the Indonesia Stock Exchange. The research method used is the comparative method, the sampling method used is purposive sampling, and the sample used is 13 companies. The data required is secondary data obtained from the Indonesia Stock Exchange through the website www.idx.co.id, and the data collection method uses the documentation method in the form of annual financial reports. The analysis technique used in this research is the technique of financial ratio analysis, normality test and Paired sample t-Test. The results of the Paired sample t-Test test stated that there was no significant difference before and after the company took corporate action as measured by the Current Ratio, Quick Ratio, Debt to Equity Ratio, Debt to Asset Ratio, Total Assets Turnover, Fixed Assets Turnover, Return on Equity, Return on Assets, Price to Book Value, and Price Earnings Ratio. Both from 1 year before and 1 year after, to 5 years before and 5 years after the company take corporate action. Personal motive is a factor that needs to be considered by the company in making decisions